Histologic outcomes in HPV-positive and cervical cytology-negative women - screening results in Northern Thailand - Linlada Vijakururote (2018)
The objective of this study was to determine the prevalence of significant lesions defined as high grade squamous intraepithelial lesions (HSIL), adenocarcinoma in situ (AIS) and invasive carcinoma in women who had HPV-positive and cytology negative co-testing screening results. This retrospective study was conducted in Chiang Mai University Hospital between May, 2013 and August, 2014. Hybrid capture 2 (HC2) was used for HPV testing and conventional Pap smears for cytologic screening. A repeat liquid-based cytology (LBC) was performed in women with such co-testing results followed by colposcopy. Random biopsy was performed in cases of normal colposcopic findings. Further investigations were carried out according to the biopsy or the repeat LBC results. During the study period, 273 women met the criteria and participated in the study. The mean age of these women was 46.4 years with 30% of them reporting more than one partner. The median interval time to colposcopy was 165 days. About 40% showed an abnormality in the repeat cytology. Significant cervical lesions were found in 20 (7.3%) women, including 2 invasive cancers. Of interest was that only 2 of 20 significant lesions were diagnosed by colposcopic examination while the remainder were initially detected by cervical biopsy and abnormal repeat cytology. In conclusion, the prevalence of significant cervical lesions in HPV positive and cytology negative women in Northern Thailand was 7.3%. Further diagnostic work up with repeat cytology follow by colposcopy is recommended. Random biopsy should be performed even when the colposcopic findings are normal.